STEAM AS A FACTOR OF INDIVIDUAL SYSTEMS THINKING DEVELOPMENT FOR STUDENTS OF ELECTRONICS SPECIALITY - Yakymenko, Yuriy; Poplavko, Yuriy; Lavrysh, Yuliana (Advanced Education, 2020)
The present paper addresses the issue of teaching electronics as an integrative course at university. One of the urgent demand to universities is to prepare future specialists for solving multi-tasked global problems. Therefore, educators need to employ new teaching strategies and methods. Systems thinking skills are considered as the requirement of the twenty-first century that should be developed at universities. We suggest STEAM approach as a powerful tool to foster the development of individual systems thinking skills in students of electronics speciality. In order to verify our hypothesis, we assessed students’ level of system thinking skills and employed systems thinking tools development during teaching field-related and English language classes to accomplish STEAM as an approach that supports individual types of information perception through technical, creative, scientific cognitive skills. Our assumption was confirmed by the results of the post-test. Among the skills that were changed: information needs and general resources identification, feasibility and sustainability of solution assessment, root causes identification and perspectives evaluation. We also identified the most efficient practical tools and differentiated them by subjects. Due to these transformations, we are able to develop technological literacy and foster cognitive skills such as creative, critical and systems thinking for problem-solving process.